Coracoid osteotomy approach for open free bone grafting of anterior glenoid defects - Adrik Z. Da Silva, BS; Michael A. Moverman, MD; Mitchell Yelton, BS; Joshua Mizels, MD; John C. Wheelwright, MD; Christopher D. Joyce, MD; Robert Z. Tashjian, MD (JSES Reviews, Reports, and Techniques)
The utilization of free bone grafts to reconstruct large anterior glenoid defects has increased. Distal tibia allograft is commonly used due to its lack of donor site morbidity, ability to restore large bony defects, and near anatomic osteoarticular restoration. However, the intact coracoid and conjoint tendon often impair adequate visualization and access to perform an anatomic reconstruction during open free bone graft reconstruction and often requires violation of the subscapularis tendon to gain exposure. We present a surgical technique wherein we perform a coracoid osteotomy and subsequent repair to improve visualization when performing an open free glenoid bone graft in the setting when a patient has not undergone a prior coracoid transfer that does not require violation of the subscapularis tendon. This technique demonstrates excellent functional outcomes as well as radiographic healing of the coracoid osteotomy without pain or prominent hardware at the coracoid.